Maternal deaths databases analysis: Ecuador 2003-2013 - Antonio Pino; María Albán; Alejandra Rivas; Erika Rodríguez (SAGE Publishing, 2016)
Background: Maternal mortality ratio in Ecuador is the only millennium goal on which national agencies are still making strong efforts to reach 2015 target. The purpose of the study was to process national maternal death databases to identify a specific association pattern of variable included in the death certificate. Design and methods: The study processed mortality databases published yearly by the National Census and Statistics Institute (INEC). Data analysed were exclusively maternal deaths. Data corresponds to the 2003-2013 period, accessible through INEC's website. Comparisons are based on number of deaths and use an ecological approach for geographical coincidences. Results: The study identified variable association into the maternal mortality national databases showing that to die at home or in a different place than a hospital is closely related to women's socioeconomic characteristics; there was an association with the absence of a public health facility. Also, to die in a different place than the usual residence could mean that women and families are searching for or were referred to a higher level of attention when they face complications. Conclusions: Ecuadorian maternal deaths showed Patterns of inequity in health status, health care provision and health risks. A predominant factor seems unclear to explain the variable association found processing national databases; perhaps every pattern of health systems development played a role in maternal mortality or factors different from those registered by the statistics system may remain hidden. Some random influences might not be even considered in an explanatory model yet.